2018
DOI: 10.1377/hlthaff.2017.1591
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Of Likely Precision Medicine Initiative Participants Drawn From A Large Blood Donor Population

Abstract: A goal of the Precision Medicine Initiative All of Us Research Program (AoURP) is recruitment of participants who reflect the diversity of the US. Recruitment from among blood bank donors, which may better reflect the demographic makeup of local communities, is one proposed strategy. We evaluated this strategy by analyzing the results of a survey of San Diego Blood Bank donors conducted in November 2015. Whites were more likely than nonwhites to respond to the survey (7.1 percent versus 3.9 percent). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Less favorable views about the value of research predicted a lower willingness to participate in research (Bloss et al, 2018). Importantly, while some studies reported a correlation between being a member of a racial/ethnic minority group (Hispanic, African American, or Asian American) and decreased willingness to participate (n = 5; Aagaard-Tillery et al, 2006;Bloss et al, 2018;Dye et al, 2016;Hensley Alford et al, 2011;Sanderson et al, 2017), other studies found that race and ethnicity were not predictors of consent for research…”
Section: Subtheme C: Predictors Of Participationmentioning
confidence: 98%
See 4 more Smart Citations
“…Less favorable views about the value of research predicted a lower willingness to participate in research (Bloss et al, 2018). Importantly, while some studies reported a correlation between being a member of a racial/ethnic minority group (Hispanic, African American, or Asian American) and decreased willingness to participate (n = 5; Aagaard-Tillery et al, 2006;Bloss et al, 2018;Dye et al, 2016;Hensley Alford et al, 2011;Sanderson et al, 2017), other studies found that race and ethnicity were not predictors of consent for research…”
Section: Subtheme C: Predictors Of Participationmentioning
confidence: 98%
“…Factors that clearly predicted a higher likelihood of participating in research included greater perceived benefits and values to participating in research (Bloss et al, 2018;Halbert et al, 2006;Sanderson et al, 2017), fewer concerns about the limitations and risks of research (Halbert et al, 2006;Sanderson et al, 2017), greater willingness to share personal health information (Bloss et al, 2018), fewer informational needs (Sanderson et al, 2017), and higher satisfaction with healthcare providers (Sheppard et al, 2018). Less favorable views about the value of research predicted a lower willingness to participate in research (Bloss et al, 2018).…”
Section: Subtheme C: Predictors Of Participationmentioning
confidence: 99%
See 3 more Smart Citations